19th century ornamented metal trays from Greece and Turkey: metallurgy and provenance. Issue 2 (15th December 2017) - Kotzamani, Despoina; Kantarelou, Vasiliki; Karatasios, Ioannis; Zacharia, Maria
ABSTRACT: Twelve 'Japanned' metal trays from Greece and Turkey, dated in the 19 th century, were subjected to macroscopic and microscopic examination (stereoscopy, metallography, scanning electron microscopy) as well as to XRF and SEM-EDX analysis. The trays represent two stylistic types made of wrought iron either tin-plated or protected with a primer. Two were manufactured by forging while the rest were made by rolling prior to die forming with drop hammers or machine presses. Wrought iron was produced indirectly from cast iron with fossil fuels. Only in one case charcοal fuel was implied. Most pure iron was recognized for four trays dated at the end of the 19 th century. Three of them also revealed the deliberate incorporation of metallic manganese while one of them was found to be alloyed. The other metals used such as copper, brass, silver and tin as also the methods applied, seem to follow the industrial evolution of the iron substrate but more analysis is required. As regards origin,  the metallurgical results, even limited, combined with historical information, indicated that the metals/techniques used, were probably originally produced in west Europe although the supply of materials could have depended on different sources.